Proteins P24 and P41 Function in the Regulation of Terminal-Organelle Development and Gliding Motility in Mycoplasma pneumoniae - Hasselbring, Benjamin M. (American Society for Microbiology (ASM), 2007)
Mycoplasma pneumoniae is a major cause of bronchitis and atypical pneumonia in humans. This cell wall-less bacterium has a complex terminal organelle that functions in cytadherence and gliding motility. The gliding mechanism is unknown but is coordinated with terminal-organelle development during cell division. Disruption of M. pneumoniae open reading frame MPN311 results in loss of protein P41 and downstream gene product P24. P41 localizes to the base of the terminal organelle and is required to anchor the terminal organelle to the cell body, but during cell division, MPN311 insertion mutants also fail to properly regulate nascent terminal-organelle development spatially or gliding activity temporally. We measured gliding velocity and frequency and used fluorescent protein fusions and time-lapse imaging to assess the roles of P41 and P24 individually in terminal-organelle development and gliding function. P41 was necessary for normal gliding velocity and proper spatial positioning of new terminal organelles, while P24 was required for gliding frequency and new terminal-organelle formation at wild-type rates. However, P41 was essential for P24 function, and in the absence of P41, P24 exhibited a dynamic localization pattern. Finally, protein P28 requires P41 for stability, but analysis of a P28(−) mutant established that the MPN311 mutant phenotype was not a function of loss of P28.